A Research Agenda for Small and Medium-Sized Towns - Mayer, Heike (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. Exploring current debates on the topic, this book maps out an agenda for theory, research and practice about the role and function of small and medium-sized towns in various contexts and at different territorial scales. Chapters highlight new insights and approaches to studying small and medium-sized towns, moving beyond the 'urban bias' to provide nuanced thought on these spaces both in terms of their relation to larger cities, and in terms of implications related to their size.